1998
DOI: 10.1038/nm0798-802
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 is a new form of tumor suppressor with true haploid insufficiency

Abstract: Components of the transforming growth factor-beta (TGF-beta) signal pathway function as classic tumor suppressors, but the role of the TGF-betas themselves is less clear. Here we show that mice heterozygous for deletion of the TGF-beta1 gene express only 10-30% of wild-type TGF-beta1 protein levels. Although grossly normal, these mice have a subtly altered proliferative phenotype, with increased cell turnover in the liver and lung. Treatment of these mice with chemical carcinogens resulted in enhanced tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
210
1
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(222 citation statements)
references
References 35 publications
8
210
1
3
Order By: Relevance
“…Importantly, there remains a significant reduction in the ability of breast cancer cells to establish or grow in TGF-b1 þ /À; RAG2À/À tibiae compared with wild-type controls. This dramatic effect in TGF-b1 þ /À; RAG2 À/À mice may reflect the fact that TGF-b1 protein levels have been found to be reduced up to 60-90% of the levels observed in wild-type mice without a concomitant upregulation of TGF-b2 or TGF-b3 (Tang et al, 1998). Thus, our results show that the reduced levels of TGF-b1 can have a profound effect on the ability of breast cancer cells to establish or grow in bone.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, there remains a significant reduction in the ability of breast cancer cells to establish or grow in TGF-b1 þ /À; RAG2À/À tibiae compared with wild-type controls. This dramatic effect in TGF-b1 þ /À; RAG2 À/À mice may reflect the fact that TGF-b1 protein levels have been found to be reduced up to 60-90% of the levels observed in wild-type mice without a concomitant upregulation of TGF-b2 or TGF-b3 (Tang et al, 1998). Thus, our results show that the reduced levels of TGF-b1 can have a profound effect on the ability of breast cancer cells to establish or grow in bone.…”
Section: Discussionmentioning
confidence: 94%
“…Approximately 72% of the tibial injections in TGF-b1 þ / þ ; RAG2À/À gave rise to osteolytic lesions compared with only 44% in TGF-b1 þ /À; RAG2À/À mice and 33% in TGF-b1À/À; RAG2À/À animals ( Figure 3b). The dramatic effect observed in TGF-b1 þ /À; RAG2À/À mice most likely reflects the fact that TGF-b1 protein levels are reduced up to 60-90% of the levels observed in wild-type mice (Tang et al, 1998). Interestingly, bioluminescence imaging showed that MDA-MB-231 breast cancer cells capable of establishing themselves in TGF-b1 þ / þ ; RAG2À/À, TGF-b1 þ /À; RAG2À/À and TGF-b1À/À; RAG2À/À mice grew out at similar rates ( Figure 4a) and induced similar degrees of osteolytic bone destruction (Figure 4b).…”
Section: Tgf-b-neutralizing Ligand Trap Impairs Signaling Induced By mentioning
confidence: 97%
“…Accordingly, TGF-b1 þ /À mutant mice are significantly more susceptible (3.2-fold) to diethylnitrosamine and phenobarbital after 9 months of treatment compared with wild types (Tang et al, 1998). In addition, transgenic mice overexpressing a dominant negative TBRII exhibit significant increase in incidence, size and multiplicity of preneoplastic lesions and of HCCs (Tang et al, 1998;Kanzler et al, 2001). Also, in chronic hepatitis C infection, HCV-derived core protein associates with the Smad3 MH1 domain inhibiting its DNA-binding activity (Pavio et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Given its antiproliferative role in various epithelial cells as well as in liver, the TGF-b signaling likely suppresses hepatocellular carcinogenesis. Accordingly, TGF-b1 þ /À mutant mice are significantly more susceptible (3.2-fold) to diethylnitrosamine and phenobarbital after 9 months of treatment compared with wild types (Tang et al, 1998). In addition, transgenic mice overexpressing a dominant negative TBRII exhibit significant increase in incidence, size and multiplicity of preneoplastic lesions and of HCCs (Tang et al, 1998;Kanzler et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted deletion of TGF-b1 gene predisposes mice to the development of squamous cell carcinoma (Glick et al, 1994). Hemizygous or homozygous Tgfb1-null animals show increased incidence of chemically or spontaneously induced tumors (Tang et al, 1998). Several components of the TGF-b signaling pathway have been found to act as tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%